2017
DOI: 10.1021/acs.jpcc.6b12572
|View full text |Cite
|
Sign up to set email alerts
|

Disappearance of Localized Valence Band Maximum of Ternary Tin Oxide with Pyrochlore Structure, Sn2Nb2O7

Abstract: The electronic structure of ternary tin oxide with pyrochlore structure, Sn 2 Nb 2 O 7 , which has the contribution of the Sn 5s orbitals in the valence band, is examined by synchrotron-radiation-excited photoelectron spectroscopy and X-ray absorption spectroscopy together with ab initio calculations. The empirical spectra are qualitatively consistent with the calculated density of states with the exception of a striking discrepancy in the electronic structure around the valence band maximum (VBM). The band ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 40 publications
3
25
0
Order By: Relevance
“…•• formation, occurs preferentially around the Sn ions. These findings are supported by our preliminary calculations on the defect formation energy [16].…”
Section: Comparing the Formation Of Oxygen Vacancies Through Crystal ...supporting
confidence: 87%
See 1 more Smart Citation
“…•• formation, occurs preferentially around the Sn ions. These findings are supported by our preliminary calculations on the defect formation energy [16].…”
Section: Comparing the Formation Of Oxygen Vacancies Through Crystal ...supporting
confidence: 87%
“…Recently, we developed novel p-type Sn 2+ oxides, namely, SnNb 2 O 6 and Sn 2 Nb 2 O 7 , with a band gap of 2.4 eV (Figure ). Although their valence band is composed of a Sn 5s orbital, they showed a low hole mobility of 0.03–0.4 cm 2 V –1 s –1 . , In general, because structural defects act as the scattering centers for electrons (holes), the mobility decreases with the increase in the defect density; hence, the reduction of these defects is a common strategy for increasing the hole mobility . At the same time, the carriers are generated by the defect formations, and therefore, a high carrier generation efficiency of the donor (acceptor) is required to improve the hole mobility for practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Photoemission spectra of this sample did not show the sharp peak predicted by the expected FB. Møssbauer spectroscopy revealed that this sample had a large amount of Sn deficiency [51]. This deficiency may greatly affect FB, and it is expected that a less Sn-deficient sample may cause unusual magnetic properties.…”
Section: Resultsmentioning
confidence: 99%
“…The compounds (b) Sn 2 Nb 2 O 7 and (c) Bi 2 Ti 2 O 7 have already been synthesized [19][20][21][22][23], while (a) Tl 2 Mo 2 O 7 has not been reported yet. However, an analogous pyrochlore oxide Tl 2 Ru 2 O 7 has been already synthesized and shows unique metal-insulator transition [24].…”
Section: Introductionmentioning
confidence: 99%